Use of the computational topology to analyze the pore space changes during chemical dissolution - Khachkova, T.S.; Bazaikin, Ya.V.; Lisitsa, V.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2020)
A new algorithm for constructing the persistence diagrams to estimate the changes in the rock matrix topology during the chemical fluid-solid interaction. In the space of the persistence diagrams, a metric is introduced, which allows one to clusterize the diagrams in order to estimate their dissimilarities in the topology changes. This clusterization shows that the main parameters affecting the topology of the rock matrix are the reaction rate and the diffusion coefficient, whereas the fluid flow rate makes a smaller effect on the topology.